Students’ perception on disciplinary measures in public secondary schools in Kedah, Malaysia: A case study - Lee, J.C.; Mohan, R.; Abdul Halim, M.; Mua’azam, M. (Penerbit Akademia Baru, 2017)
Facing and dealing with discipline problems caused by secondary schools students probably among the most difficult and unpleasant part of teaching profession. Disciplinary measures adopted for ensuring discipline has been a very challenging encounter. School administrators and teachers have often overlooked, marginalized or even neglected the inclusion of an important component, “the student’s opinion” in seeking solutions for problems pertaining to student related matters. It is only rational or rather logical to ask the most informed group that is the students themselves on what they actually think or feel regarding issues directly concerning their welfare. This study therefore, explores the perception of secondary school students on disciplinary measures imposed by the school authority. 1200 secondary school students from 24 secondary schools were purposively selected. The study findings revealed that even though majority of the students in this study perceived that some disciplinary measures imposed were unfair, unreasonable and unsuitable, interestingly, the same students perceived that those disciplinary measures will decrease their indiscipline behaviors in future. Among all the disciplinary measures imposed, counselling yielded the highest percentage of agreement that it is fair, reasonable and suitable for the students. This suggests that in order to deal with indiscipline behavior caused by the students in secondary school, counselling approach is essential.